Losing Steam: The Boiler and Engine Industry as an Index of British Columbia’s Deindustrialization, 1880‑1915 - Lutz, John (Historical Papers / Communications historiques, 1988)
AbstractThis paper examines the process whereby the resource industries on the BritishColumbia frontier were disconnected from the local secondary manufacturing industriesand coupled to the growing manufacturing economies of southern Ontario, the UnitedStates, and Great Britain between 1860 and 1915. The resource extractive industrieswere closely linked, in British Columbia, to the boiler and engine-making industry andprior to 1900 both sectors grew apace. After 1900 the growing demand for boilers andengines was met by producers in Ontario, the United States, and Britain while the BritishColumbia industry went into decline. An examination of both the costs of productionand the social determinants of those costs reveals that the main causes of thisdisplacement were the linking of the high-wage British Columbia economy to the lowerwage east by the Canadian Pacific Railway; the railway's discriminatory rate structure;and a shift towards nonlocal ownership of the main components in the economy whichwas accompanied by new purchasing patterns that favoured nonlocal secondarymanufacturers.